Soda veidu attīstība, daudzveidība un nozīme Krimināllikumā - Stira, Zane (Latvijas Universitāte, 2016)
Gluži tāpat, kā noziedzība pastāvējusi kopš radās sabiedrība, tāpat tai līdzās eksistē sods, kas evolucionējis līdz ar sabiedrības izpratni par tā nozīmi un mērķi. Autore darbā noskaidro, kas vispār ir sods, kāpēc tas vajadzīgs un kādam tam jābūt, lai efektīvi sasniegtu soda mērķi. Tāpat darbā analizēti sodu veidi Krimināllikumā un rastas atbildes tam, vai tajā esošie sodu veidi ir atbilstoši mūsdienu vajadzībām. Kā arī tiek meklēti jauni alternatīvi soda veidi, kurus būtu iespējams ieviest Latvijas sodu sistēmā. Atslēgvārdi: sods, soda mērķis, sodu sistēma, sodu veidi, soda veidu trūkumi un alternatīvas.

Just as crime existed since the society originated, at the same time alongside with it exists punishment, which comes precisely to the public understanding of its meaning and purpose. The author clarifies in this paper what is punishment, why it is needed and what it should be, in order to effectively achieve the purpose of punishment. Similary, in the paper author analyses the types of punishments in the Criminal Law in order to find an answer as to whether the existing types of punishments are appropriate for today's needs. Also in this paper author seeks new alternative types of punishments that may be possible to introduce in Latvian penal system. Keywords: punishment, purpose of punishment, the system of punishments, types of punishment, disadvantages and alternatives of types of punishments.
Type of sentence development, diversity and importance of the Criminal Law
Keywords: Juridiskā zinātne